How does climate exacerbate root causes of conflict in Sudan? Climate Security Pathway Analysis - Sax, Niklas; Hassan, Gamal Mohamed; Abdi, Abdimajid Nunow; Madurga Lopez, Ignacio M.; Carneiro, Bia; Liebig, Theresa Ines; Läderach, Peter R.D.; Pacillo, Grazia (CGIAR System Organization, 2023)
This factsheet gives answers on how climate exacerbates root causes of conflict in Sudan, using an impact pathway analysis. Two main impact pathways are identified: 1. Resource Availability and Access: Climate variability and extreme events are putting pressure on land, water and pasture while increasing desertification is pushing pastoralists ever further south in their quest to feed their livestock. 2. Livelihood and Food Security: Climate variability is reducing agricultural production in Sudan, leading to high food insecurity and protests.